A strategic management paper for DLS-College of Saint Benilde - Rivero, Francisco D. (Animo Repository, 2007)
In respect of the concept of equality of educational opportunity and accessibility there is no denying that leaders in the developing countries generally understand the importance of investing in basic and general education. They also recognize that high levels of literacy, numeric and computer knowledge in the technological era of the next millennium are critical prerequisites for creating a competitive workforce and a nation of educated workers and active citizens